UZBEKISTAN AS A PILLAR OF REGIONAL STABILITY IN CENTRAL ASIA - Rabbimov , Og'abek (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
This paper explores Uzbekistan’s evolving role as a key actor and stabilizing force in Central Asia. Since gaining independence, Uzbekistan has undergone significant political, economic, and social transformations, which have contributed to its increasing influence within the region. In particular, the post-2016 era marked by reforms, regional cooperation, and a proactive foreign policy has positioned Uzbekistan as a pillar of stability amidst complex geopolitical dynamics. The paper analyzes Uzbekistan’s contributions to regional security, cross-border cooperation, economic integration, and conflict prevention, emphasizing its strategic importance in maintaining peace and sustainable development in Central Asia.